Gain-Scheduled Robust Recursive Lateral Control for Autonomous Ground Vehicles Subject to Polytopic Uncertainties - Bueno, José; Rocha, Kaio; Terra, Marco (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This paper addresses the lateral control problem for autonomous ground vehicles. In order to better capture the behavior of lateral dynamics, the model is subject to polytopic uncertainties based on different road and load conditions. These uncertainties can potentially degrade the performance of the system and, as a consequence, endanger passengers, pedestrians and surrounding vehicles. It is crucial, then, that the controller handles these parametric deviations to preserve safety and stability. To this end, a robust recursive control algorithm computes a set of feedback gains that minimizes the trajectory tracking error state. Meanwhile, a gain-scheduling strategy interchanges among these recursive gains at each instant. A numerical simulation is also provided to illustrate the effectiveness of the proposed method.